Fair trade? : High frequency trading in the light of just consequentialism - Korhonen, Minna (My University, 2018)
HF trading can be viewed as part of the digitalization of financial markets, a transformation extend-ing from tools to trading methods and even behaviors of market participants. In this thesis, HF trad-ing was approached via two distinct concepts of market integrity and fairness. A traditional litera-ture review was conducted with special emphasis on the consequences of HF trading, debate on market integrity and fairness aspect on HF trading, and the recent regulatory developments sur-rounding the topic. The findings of literature review were then subjected to analysis based on J.H. Moor’s theory on just consequentialism. Following the increase of speed and automatization, the risks of malfunction and systemic incidents are evident and should not be ignored. Thus, the findings of the thesis strongly indicate that mitigat-ing these risks by regulatory measures such as enforcing monitoring, reporting and increased trans-parency are well justified if not mandated. These themes also seem to appear regularly in recently introduced laws and policies governing HF trading. Moreover, the speed and processing power characteristic to HF trading leave open questions regarding the fairness of trading activity as well as the possibility of negative externalities to non-HF market participants. However, considering the lack of long-term research evidence on the effects of HF trading, the complexity of causal relation-ships within the modern financial system and the endogenous nature of haves and have nots be-tween market participants, determining HF trading as (un)ethical was not possible within the scope of the thesis.
Keywords: HF trading, high frequency trading, ethics, computer ethics, AI